Análisis de la gestión financiera y la liquidez de la distribuidora DYG de la cuidad de Babahoyo del periodo 2020 - Zuñiga Acosta, Joshua Ruben (2021)
The DYG distributor is located in the Babahoyo canton of the rivers province, The present case study aims to analyze the financial management and liquidity of the DYG distributor of the city of Babahoyo for the 2020 Period through horizontal and vertical analysis , and the financial reasons corresponding to it, the applied methodology is the deductive and inductive method, the information presented was acquired through website documents, book, financial reasons will also be applied. Financial management is very important since by analyzing it we can verify the resources that the company has and at the same time set a fund to invest it again. Financial management is also very important since it involves the income and expenses attributable to the management of the money of companies or organizations, and therefore the profitability generated by these financial institutions. At present, every business, no matter how small, has the need to keep its income and expenses, allowing to know the financial management that it is managing, and above all to take care of its resources.